Innovation and institutional ownership - Philippe Aghion; John Van Reenen; Luigi Zingales (Fondazione Eni Enrico Mattei (FEEM), 2010)
We find that institutional ownership in publicly traded companies is associated with more innovation (measured by cite-weighted patents). To explore the mechanism through which this link arises, we build a model that nests the lazy-manager hypothesis with career-concerns, where institutional owners increase managerial incentives to innovate by reducing the career risk of risky projects. The data supports the career concerns model. First, whereas the lazy manager hypothesis predicts a substitution effect between institutional ownership and product market competition (and managerial entrenchment generally), the career-concern model allows for complementarity. Empirically, we reject substitution effects. Second, CEOs are less likely to be fired in the face of profit downturns when institutional ownership is higher. Finally, using instrumental variables, policy changes and disaggregating by type of owner we find that the effect of institutions on innovation does not appear to be due to endogenous selection.
Keywords: G20; G32; O31; O32; O33; 330; Career Concerns; Innovation; Institutional Ownership; Productivity and R&D